An analytic resolution to the competition between Lyman-Werner radiation and metal winds in direct collapse black hole hosts - Agarwal, Bhaskar; Klessen, Ralf S.; Regan, John (Monthly notices of the Royal Astronomical Society, 2017)
A near pristine atomic cooling halo close to a star forming galaxy offers a natural pathway for forming massive direct collapse black hole (DCBH) seeds, which could be the progenitors of the z > 6 redshift quasars. The close proximity of the haloes enables a sufficient Lyman-Werner flux to effectively dissociate H2 in the core of the atomic cooling halo. A mild background may also be required to delay star formation in the atomic cooling halo, often attributed to distant background galaxies. In this paper, we investigate the impact of metal pollution from both the background galaxies and the close star forming galaxy under extremely unfavourable conditions such as instantaneous metal mixing. We find that within the time window of DCBH formation, the level of pollution never exceeds the critical threshold (Zcr ∼ 1 × 10−5 Z⊙) and attains a maximum metallicity of Z ∼ 2 × 10− 6 Z⊙. As the system evolves, the metallicity eventually exceeds the critical threshold, long after the DCBH has formed.